Monetary policy switching and indeterminacy - Jean Barthélémy; Magali Marx (Quantitative Economics, 2019)
This paper determines conditions for the existence of a unique rational expectations equilibrium-determinacy-in a monetary policy switching economy. We depart from the existing literature by providing such conditions considering all bounded equilibria. We then apply these conditions to a new Keynesian model with switching Taylor rules. First, deviation from the Taylor principle in one regime does not necessarily cause indeterminacy. Second, very different responses to inflation may trigger indeterminacy even if both regimes satisfy the Taylor principle. Determinacy thus results from the adequacy between monetary regimes rather than the determinacy of each of them taken in isolation.
Keywords: E31; E43; E52; 330; Markov-switching; indeterminacy; monetary policy